Role of Interleukin-6 and Interleukin-8 Cytokines as Early Diagnostic Markers of Sepsis - Moniruzzaman, Mohammad; Chowdhury, Ashesh Kumar; Ahsan, ASM Areef; Rahman, Md Zakiur; Rumana, Saimun Nahar; Yusuf, Md Abdullah; Saha, Gobindo Chandra (Bangladesh Journal of Infectious Diseases, 2020)
Background: Rapid diagnosis is essential for effective therapy among the patients with sepsis. Objectives: The purpose of the present study was to determine the relationship of serum levels of IL-6, IL-8 in patients with various stages of sepsis. Methodology: This case control study was conducted in the Department of Immunology at Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Dhaka from January 2015 to December 2015 for a period of one (01) year. All patients had been selected from the ICU of BIRDEM General Hospital with known clinicopathological parameters of sepsis. Serum levels of IL-6 and IL-8 were assessed using Enzyme Linked Immunosorbent Assay (ELISA) method. Results: In this study, a total of 80 subjects was enrolled of which 60 patients were with at least 2 SIRS criteria and 20 healthy age matched controls without SIRS. Significant difference was found in IL-6 and IL-8 values in the patients with bacteriological culture positive and negative group (p<0.05). AUC for IL-6 was 0.710 (95% CI 0.580-0.840), sensitivity 54.16%, specificity 59.09%, PPV 74.28% and NPV 52% with cutoff value >177pg/ml. Conclusion: Elevated levels of serum IL-6 and IL-8 is found in the patients with sepsis Bangladesh Journal of Infectious Diseases 2019;6(2):34-38